2005
DOI: 10.1002/jemt.20157
|View full text |Cite
|
Sign up to set email alerts
|

Occasional transsynaptic viral labeling in the central nervous system from the polycystic ovary induced by estradiol valerate

Abstract: Increased density of catecholaminergic nerves in the human polycystic ovary has been observed. The aim of the present study was to investigate the distribution of transsynaptically virus-labeled neurons in the central nervous system from the rat polycystic ovary to see whether is it different or not from that of cycling control rats. To induce a polycystic ovary, a single injection of estradiol valerate was given to adult female rats and 30 days later a neurotropic virus was injected into the right ovary. Rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
2
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
(40 reference statements)
2
2
0
Order By: Relevance
“…Our data on androgenized female rats are consistent with those of previous studies (1)(2)(3)(4)(5)(11)(12). Our findings suggest the animals had altered ovulation and even an absence of ovulation.…”
supporting
confidence: 95%
“…Our data on androgenized female rats are consistent with those of previous studies (1)(2)(3)(4)(5)(11)(12). Our findings suggest the animals had altered ovulation and even an absence of ovulation.…”
supporting
confidence: 95%
“…It is interesting to note that the effect of EV was not found at the celiac ganglion. Probably, the estradiol effect is preferentially localized to the ovarian nerves and does not involve the central sympathetic control, as demonstrated previously [30]. Ovarian NGFB concentration in adult rats was lower than that in controls.…”
supporting
confidence: 53%
“…Viral transneuronal tracing studies [30] have demonstrated that EV effect does not involve sympathetic neurons projecting from the hypothalamic paraventricular nucleus, thus supporting a local effect of estradiol on the expression of intraovarian neurotrophic factors. The rapid effect of EV on Ngfb and Ngfr mRNA expression found in our study could be the result of the estrogen action on the estrogen response elements present in the DNA for Ngfb and Ngfr [31].…”
Section: Short-term Effect Of Neonatal Ev Administration On the Exprementioning
confidence: 98%
“…Indeed, neonatal estradiol-induced increases in glutamate neurotransmission have been clearly demonstrated to occur during puberty (32). The administration of estradiol to adult rats using the same protocol used in the present study produced a deleterious effect on noradrenergic neurotransmission (34,35) and a neurodegenerative effect on opioid neurons in the hypothalamus (36). Therefore, we are tempted to suggest that the administration of EV before the maturation of the reproductive hypothalamus produced a permanent excitatory effect that altered its functioning up to adulthood.…”
Section: Figurementioning
confidence: 71%